Using Biomedical Text as Data and Representation Learning for Identifying Patients with an Osteoarthritis Phenotype in the Electronic Medical Record. (2018) - Meaney, Christopher; Widdifield, Jessica; Jaakkimainen, Liisa; Escobar, Michael; Rudzicz, Frank; Tu, Karen
No abstract available